2021
DOI: 10.1002/art.41594
|View full text |Cite
|
Sign up to set email alerts
|

Eccentric Resistance Training Ameliorates Muscle Weakness in a Mouse Model of Idiopathic Inflammatory Myopathies

Abstract: Objective. High-force eccentric contractions (ECCs) have traditionally been excluded from rehabilitation programs that include patients with idiopathic inflammatory myopathies (IIMs) due to unverified fear of causing muscle damage and inflammation. In an IIM animal model that used mice with experimental autoimmune myositis (EAM), we undertook this study to investigate whether ECC training can safely and effectively be used to counteract muscle weakness in IIM.Methods. EAM was induced in BALB/c mice by immuniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
2
5
0
Order By: Relevance
“…Indeed, our data show that HIIT inhibited the increased amount of ER stress proteins Grp78, Grp94, and PERK in the skeletal muscle of EAM mice. This is in line with a previous study from our lab where EAM-induced upregulation of ER stress proteins, including Grp78 and Grp94, was attenuated by 4 weeks of high-intensity eccentric contraction training in EAM mice [ 31 ]. Taken together, our findings promote exercise as an important non-pharmacological approach for relieving ER stress and improving mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Indeed, our data show that HIIT inhibited the increased amount of ER stress proteins Grp78, Grp94, and PERK in the skeletal muscle of EAM mice. This is in line with a previous study from our lab where EAM-induced upregulation of ER stress proteins, including Grp78 and Grp94, was attenuated by 4 weeks of high-intensity eccentric contraction training in EAM mice [ 31 ]. Taken together, our findings promote exercise as an important non-pharmacological approach for relieving ER stress and improving mitochondrial function.…”
Section: Discussionsupporting
confidence: 92%
“…EAM is induced by immunization with three injections of myosin emulsified in complete Freund’s adjuvant. Muscle function is impaired at the end of the immunization period where muscular inflammation is already established [ 31 , 32 ]. Intriguingly, we recently have reported that resistance training starting 1 day after the last immunization inhibits ER stress and restores muscle strength in mice with EAM [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). This finding suggests that weakness in IIMs may, at least in part, be caused by dysfunction of the contractile apparatus, and has also been illustrated in mouse models (Coley et al 2012;Himori et al 2021).…”
Section: Introductionmentioning
confidence: 62%
“…A similar effect has been described in mice with experimental autoimmune myositis, utilized as an IIM animal model. In this protocol, eccentric contractions (20 ECCs every other day for 4 weeks) in electrically-stimulated plantar flexor muscles prevented the decrease in force and the increase in endoplasmic reticulum (ER) stress proteins seen in untrained animals and also enhanced the expression and myofibrillar binding of HSPB1 and HSPPB5 [ 174 ].…”
Section: Putative Role Of Exercise-induced Modulation Of Hspb5 In The...mentioning
confidence: 99%